PENGGUNAAN TWITTER DALAM BELAJAR KOSAKATA BAHASA INGGRIS (PERSEPSI MAHASISWA) - RAMBITAN, RIMA ROMANSI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This research entitled â€œPenggunaan Twitter dalam Belajar Kosakata Bahasa Inggris (Persepsi Mahasiswa)â€. This research is part of second language acquisition and the objective of this research is to find out how the twitter users of English students at Faculty of Letters Sam Ratulangi University increase their vocabulary in English. Â  A qualitative research was used in this research to answer research question and the Blachowicz and Fisherâ€™s theory is used in this research. The research took 25 students as samples. The data were taken through questionnaire and open ended questions (interview). The result shows that according to most of studentâ€™s perception student can be active in developing their understanding of words and ways to learn vocabulary through twitter, students can personalize word learning through twitter can immerse in words through twitter, can build on multiple sources of information to learn words through repeated exposure by reading tweets in twitter. This result supports the four principles which stated by Blachowicz and Fisher (2000), and it gives positive effect to students. Â  Keywords: Vocabulary Learning, Twitter, Student Perception